The current situation and future prospects of beer export from Iceland - Haukur Guðmundsson 1988- (2017)
This study analyses the Icelandic beer market in terms of exports and the objective of the research is to find out how Icelandic beer breweries are creating new foreign markets and how the development has been in terms of beer exports from Iceland in the years 2007-2016. The main markets of Icelandic beer in Europe and the United States are also analysed and the future prospects of beer exports from Iceland are discussed. The beer industry in Iceland has been blooming in that time with many breweries starting operations. This study is carried out using a qualitative research method and semi structured in depth interviews that were conducted with representatives of five Icelandic breweries to discuss their foreign operations. The seven stages of interview inquiry framework by Brinkman & Kvale was followed during all steps of the research. The main results of this research are that exports of beer have increased greatly in the period and that the United States and Britain are the main markets for Icelandic beer. The Icelandic breweries use indirect export as a way to enter foreign markets and foreign intermediaries handle sales and marketing of their products in foreign markets. The main challenges for Icelandic breweries in terms of export are high transportation costs and the fluctuations of the Icelandic currency and increasing competition in foreign markets are also challenging for the breweries. The motives for export are mainly reactive when it comes to export, but there seems to be a difference in how the smaller breweries and the larger breweries work. The larger breweries are working more proactively than the smaller ones which might be explained with more access to resources and more qualified staff with expertise in exporting. The positive image of Iceland has been very valuable for the breweries and it has helped the companies to create new foreign markets. Þessi rannsókn greinir íslenska bjórmarkaðinn með tilliti til útflutnings og markmið rannsóknarinnar er að komast að því hvernig íslensk ...